The contribution of mathematics to Islamic civilization: A historical study and its relevance in the modern era - Hidayatulloh, Bagus; Nurwahid, Mohammad (Privietlab, 2025)
This article discusses the contribution of mathematics to the development of Islamic civilization from a historical perspective and its relevance in the contemporary context, especially in Indonesia. Using a critical review of scientific literature and relevant primary sources, this study evaluates the significant role of mathematics in shaping the social, religious, and economic systems of Muslims. Through figures such as Al-Khawarizmi, Al-Battani, and Al-Biruni, this article shows that mathematics is not only a tool for calculation, but also an instrument for upholding justice in inheritance (faraidh), sharia accounting, statistics on the welfare of the community, and measures and scales in muamalah. These concepts reflect the integration of reason and revelation in building a scientific and spiritual civilization. The relevance of these values in the modern era has been increasingly strengthened by the development of digital technology and the demand for a transparent and fair economic system. Therefore, synergy is needed between mathematics education and Islamic values as well as strengthening sharia-based digital research and applications to realize a Muslim society that is spiritually and scientifically advanced.